1979
DOI: 10.1080/00288233.1979.10420843
|View full text |Cite
|
Sign up to set email alerts
|

Response surfaces of “Kopara” wheat for seeding rate, and levels and times of application of nitrogen fertiliser

Abstract: A three factor central composite second order design in incomplete blocks was used to quantify the yield responses of 'Kopara' wheat established at five seeding rates (170-580 seeds 1m 2). and fertilised at five rates of N at the onset of tillering (0-124 kg/ha) and again during spikelet growth (0-38 kg/ha). Seeding rate increments had little effect on grain yield but optimum yields were achieved at 375 seeds/m". Increased spike populations obtained at higher seeding rates were offset by diminished grain set a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In the present study densities of 178 plants m"-' were used for both wheat and wild oats. Under normal field densities of wheat in New Zealand of 250-300 plants m"- (Dougherty, Love & Mountier, 1979), the crop could be expected to be competitive against wild oats emerging during at least the first 3 weeks. The effectiveness ofa wheat crop in preventing later-emerging wild oat plants from reaching reproductive maturity is dependent upon careful drilling and a high plant population.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study densities of 178 plants m"-' were used for both wheat and wild oats. Under normal field densities of wheat in New Zealand of 250-300 plants m"- (Dougherty, Love & Mountier, 1979), the crop could be expected to be competitive against wild oats emerging during at least the first 3 weeks. The effectiveness ofa wheat crop in preventing later-emerging wild oat plants from reaching reproductive maturity is dependent upon careful drilling and a high plant population.…”
Section: Discussionmentioning
confidence: 99%
“…Under South Island conditions on soils with higher P levels, N has a greater influence than P on fertile tiller populations where successive wheat crops are grown (McLeod 1974). Other research in the South Island has shown N increases yield by increasing the fertile tiller population (Feyter & Cossens 1977;Scott et al 1977;Dougherty et al 1978).…”
Section: Discussionmentioning
confidence: 99%